Comparison of mechanical properties between different orthodontic stainless steel archwires - Abu Bakar, Noraini; McDonald, Fraser; Tan, Lawrence (Canada, 2017)
Introduction: The Damon system recommended the use of revolutionary, hightechnology Damon edgewise 0.019” x 0.025” orthodontic stainless steel archwires (OSSA) for major mechanics and finishing and claimed that this new archwires offer greater efficiency during orthodontic treatment. No study has been carried out to compare this relatively new archwires to other popular OSSA already in the market. Aim: The aim of this study was to compare the mechanical properties of Damon 0.019” x 0.025” OSSA with Standard Ormco and 3M archwires. Method: 30 preformed archwires of each type (Standard Ormco, 3M and Damon) were tested in the as-received condition. Tensile tests were performed on a Instron Universal Testing Machine with an inter-crosshead span of 10mm. Data were obtained using Bluehill software for maximum load, automatic modulus, 0.1% yield strength and Young’s modulus. Results: For maximum load, there was no difference between Damon (Mean 659.8 ± 26.6N) and 3M (Mean 668.4 ± 9.1N), but both Damon and 3M were statistically superior compared to Standard Ormco (Mean 611.9 ± 23.2N). With respect to automatic modulus, Damon (Mean 41786.0 ± 5104.2MPa) was proven to be statistically inferior to both Standard Ormco (Mean 47318.2 ± 6106.2MPa) and 3M (Mean 49897.6 ± 3286.1MPa). For the 0.1% yield strength, there was no difference between Damon (Mean 2150.1 ± 88.6MPa) and 3M (Mean 2178.8 ± 29.6MPa), but both Damon and 3M were statistically superior compared to Standard Ormco (Mean 1990.8 ± 74.5MPa). With regard to the Young’s modulus, Damon (Mean 40598.3 ± 5077.4MPa) was proven to be statistically inferior to both Standard Ormco (Mean 44910.9 ± 5463.4MPa) and 3M (Mean 47500.7 ± 3431.6MPa). Conclusion Damon 0.019” x 0.025” OSSA were proven to be similar to 3M in maximum load and 0.1% yield strength. As for Young’s and Automatic Modulus, Damon was proven to be statistically inferior to 3M and Standard Ormco. 3M was proven to be superior in all parameters.